Methods to increase the effectiveness of maximal power training for the upper body - Baker, D.; Newton, R. U. (Strength and Conditioning Journal, 2005)
Power training recommendations have typically involved Olympic Weightlifting and plyometric exercise prescriptions, paying scant attention to upper body maximal-power demands. This article attempts to redress this situation by focusing upon strategies and specific techniques that can be implemented to enhance the effectiveness of upper body maximal-power training.